Exploring the roles and potential therapeutic strategies of inflammation and metabolism in the pathogenesis of vitiligo: a mendelian randomization and bioinformatics-based investigation - He, Ming-jie; Ran, De-long; Zhang, Zhan-yi; Fu, De-shuang; He, Qing; Zhang, Han-Yin; Mao, Yu; Zhao, Peng-Yuan; Yin, Guang-wen; Zhang, Jiang-an (Frontiers in Genetics, 2024)
Background: Vitiligo is a common autoimmune acquired pigmentary skin disorder, and its pathogenesis is not fully understood. However, there is evidence suggesting that inflammation and metabolism play a crucial role in its onset and development.The main goal is to explore the causal relationships between vitiligo and inflammatory proteins, immune cells, and metabolites, investigating potential bidirectional associations. Additionally, through bioinformatics analysis, the aim is to explore the functions and pathways of identified proteins and determine potential drug targets.Methods: Mendelian Randomization (MR) analysis was conducted on multiple datasets, including 4,907 plasma proteins, 91 inflammatory proteins, 731 immune cell features, and 1400 metabolites and metabolite ratios. Bioinformatics analysis included Protein-Protein Interaction (PPI) network construction, Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. Subnetwork discovery and identification of hub proteins were performed using the Molecular Complex Detection (MCODE) plugin in Cytoscape. Furthermore, colocalization analysis and drug target exploration, including molecular docking validation, were carried out.Results: MR analysis identified 49 proteins, 39 immune cell features, and 59 metabolites causally related to vitiligo. Bioinformatics analysis revealed significant involvement in PPI, GO enrichment, and KEGG pathways. Subnetwork analysis identified six central proteins, with interferon regulatory factor 3 (IRF3) showing strong evidence of colocalization. Molecular docking validated the binding of Piceatannol to IRF3, demonstrating a stable interaction.Conclusions: This study extensively explores the complex interactions of inflammation, immune response, and metabolism in the pathogenesis of vitiligo. Identified proteins and pathways provide potential therapeutic targets, with IRF3 considered a promising candidate. These findings contribute to a deeper understanding of the etiology of vitiligo and may guide future research and drug development efforts.